Effects of patient‐tailored atorvastatin therapy on ameliorating the levels of atherogenic lipids and inflammation beyond lowering low‐density lipoprotein cholesterol in patients with type 2 diabetes. Issue 5 (26th March 2013) - Son, Jang Won; Kim, Dong Jun; Lee, Chang Beom; Oh, Seungjoon; Song, Kee‐Ho; Jung, Chan Hee; Mok, Ji Oh; Kim, Jong Hwa; Moon, Min Kyong; Choi, Kyung Mook; Cho, Jae Hyoung; Choi, Sung Hee; et al.
Abstract Aims/Introduction Recently, patient‐tailored statin therapy was proven effective for achieving target low‐density lipoprotein (LDL) cholesterol levels. It is unclear, however, whether this therapeutic modality would be effective for atherogenic lipid profiles and inflammation in patients with type 2 diabetes. Materials and Methods The present study was an 8‐week, multicenter, single‐step titration trial of patient‐tailored atorvastatin therapy (10, 20 and 40 mg) according to baseline LDL cholesterol levels in 440 patients with type 2 diabetes. We measured the LDL particle size by polyacrylamide gel electrophoresis, and used high‐sensitivity C‐reactive protein (hsCRP) and adiponectin as surrogate markers of inflammation. Results In the intention‐to‐treat analysis, 91% of the patients achieved their LDL cholesterol targets (<2.6 mmol/L) at week 8. There were significant reductions at week 8 in total cholesterol, triglycerides, non‐high‐density lipoprotein cholesterol (HDL) cholesterol, and the total cholesterol:HDL cholesterol ratio compared with the baseline values for all of the doses. The mean LDL particle size was significantly increased, and the small, dense LDL cholesterol levels were decreased in a dose‐dependent manner over the study period. In addition, the hsCRP levels were decreased in those high‐risk patients with baseline hsCRP levels over 3 mg/L (P < 0.001), and the adiponectin levels tended to increase with all of the doses (P = 0.004) at 8 weeks. Conclusions Patient‐tailored atorvastatin therapy based on LDL cholesterol at baseline was effective in ameliorating atherogenic LDL particle size and inflammation, in addition to achieving the target LDL cholesterol level without an undesirable effect on glycemic control in patients with type 2 diabetes. This trial was registered with ClinicalTrials.gov (no. NCT01239849).